Fenomena Permasalahan Masyarakat Modern Dalam Masyarakat Risiko - Avril Hs Adila Anugrah; Claudia Laurent; Haningdia Chintya Zaki Zabrina (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2023)
A community at risk is a situation when the community experiences a sensitivity to the presence of modernization whose impact will make the community at risk, which means that the community will experience and will face various threats and uncertainty in life. Risk itself is a hazard or threat, consequences, and also the consequences that can be obtained from a process that is happening, even events that will come later. Various problems arise because of a risk. According to Beck himself, risk is the possibility of physical damage, as well as mental health, and social as a result of technological processes as well as various other processes, such as examples in communication, social and politics, even sexual. Various problems arise in society, especially in modern society caused by various things. According to Beck, there is also a physical ecological risk, which includes humans and their environment, the second is biological risk, and the third is mental risk. There are also many cases that occurred in Indonesia which caused a high risk. One example of a case that has occurred is the Covid Pandemic, which may still occur until now. This covid pandemic is often called covid-19. The outbreak of this disease first entered Indonesia in 2019. There is also a risk from technological developments, which include globalization which includes culture, the spread of hoaxes, hate speech which results in mental damage, and political lies.